1997
DOI: 10.1007/bf03346904
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an interaction between α-MSH and opioids in the regulation of gonadotropin secretion in man

Abstract: Gonadotropin secretion is inhibited by the endogenous opioids and stimulated by their antagonist naloxone. LH secretion is stimulated by alpha-MSH, a tridecapeptide derived from the post-translational processing of POMC. The possibility that alpha-MSH interacts with the opioids, as suggested by the experimental evidence, was investigated in 7 normal males aged 24-29 through the performance of seven tests: naloxone (0.8 mg i.v. bolus, followed by infusion of 1.6 mg/h for 120'); alpha-MSH (2.5 mg i.v. bolus); na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…This notion is supported by rat [19] and human [22,23] studies showing inhibition or stimulation of LH pulsatile secretion following administration of a melanocortin antagonist or agonist, respectively. We found that MTII acted much faster than leptin in restoring pulsatile LH secretion.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…This notion is supported by rat [19] and human [22,23] studies showing inhibition or stimulation of LH pulsatile secretion following administration of a melanocortin antagonist or agonist, respectively. We found that MTII acted much faster than leptin in restoring pulsatile LH secretion.…”
Section: Discussionsupporting
confidence: 53%
“…In support of this notion are the discoveries that almost all POMC cells in the ovine ARC express the leptin receptor ob/rb [5], and ovine POMC cells are activated following intravenous leptin injection (Clarke, unpublished data). Additionally, α-MSH [22] and γ-MSH [23] are capable of stimulating LH secretion in humans, and a central melanocortin receptor antagonist can reduce the effectiveness of leptin to restore gonadotropin secretion in starved rats [19]. It does, however, remain plausible that MTII elicits its effect independently of leptin signaling to rescue GnRH/LH secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to CRF secretion, the hypothalamic hormone, gonadotropin releasing hormone (GnRH), is also modulated by inhibitory tone imposed by ␤-endorphin neu- rons (Limone et al 1997). By blocking inhibitory tone imposed by ␤-endorphin, Naloxone stimulates GnRH, which in turn stimulates LH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The current observed increase in plasma testosterone is a surprising and unexpected finding. Some investigators have suggested a role for the melanocortins in the acute control of the gonadal axis (21,31,53); however, the agouti mice (2), the POMC KO mice (6), and the MC4-R KO mice (11) are all fertile, suggesting that the melanocortin system is not essential for reproduction. Our results support these findings.…”
Section: Discussionmentioning
confidence: 99%